The online evaluation of the teacher certification program using the CIPP Model - Sari, Intan Kemala; Kasmini, Lili; Rosdiana, Rosdiana; Manurung, Mayor M. H. (Jurnal Penelitian dan Evaluasi Pendidikan, 2023)
The Teacher Certification Program (PPG) is a government program to support competency improvement and standardization of teachers in Indonesia. Program organizers are LPTKs that have met the requirements for further preparation and fulfillment of human resources, infrastructure, and supporting policies. Evaluation of the PPG Program is essential, especially for LPTKs still new to implementation. Evaluation of the PPG Program is carried out using the CIPP Model, an evaluation model in terms of Context, Input, Process, and Product. The evaluation was carried out using a qualitative descriptive approach using observation, documentation, interviews, and survey instruments. The PPG program on the subject was carried out on 204 students involving 28 lecturers and 38 teachers for 94 days. The evaluation results show that the PPG Program implemented on subjects is a good and excellent value, with a context assessment directly proportional to the process and product. It is excellent, and the input assessment is good value with a comparison of students and human resources, which are still in minimum control. These results indicate that the program will be implemented very well if it fulfills the content and process aspects which are also very good for producing a product that is also very good. At the same time, the input, which consists of the number of students and human resources who have an unbalanced ratio, is not an obstacle if the implementation control is carried out as well as possible.